An antiphage Escherichia coli mutant for higher production of L‐threonine obtained by atmospheric and room temperature plasma mutagenesis. (20th August 2020) - Cheng, Likun; Wang, Jing; Zhao, Xiubao; Yin, Huanhuan; Fang, Haitian; Lin, Chuwen; Zhang, Shasha; Shen, Zhiqiang; Zhao, Chunguang
Abstract: Phage infection is common during the production of L‐threonine by E. coli, and low L‐threonine production and glucose conversion percentage are bottlenecks for the efficient commercial production of L‐threonine. In this study, 20 antiphage mutants producing high concentration of L‐threonine were obtained by atmospheric and room temperature plasma (ARTP) mutagenesis, and an antiphage E. coli variant was characterized that exhibited the highest production of L‐threonine Escherichia coli ([ E. coli ] TRFC‐AP). The elimination of fhu A expression in E. coli TRFC‐AP was responsible for phage resistance. The biomass and cell growth of E. coli TRFC‐AP showed no significant differences from those of the parent strain ( E. coli TRFC), and the production of L‐threonine (159.3 g L −1 ) and glucose conversion percentage (51.4%) were increased by 10.9% and 9.1%, respectively, compared with those of E. coli TRFC. During threonine production (culture time of 20 h), E. coli TRFC‐AP exhibited higher activities of key enzymes for glucose utilization (hexokinase, glucose phosphate dehydrogenase, phosphofructokinase, phosphoenolpyruvate carboxylase, and PYK) and threonine synthesis (glutamate synthase, aspartokinase, homoserine dehydrogenase, homoserine kinase and threonine synthase) compared to those of E. coli TRFC. The analysis of metabolic flux distribution indicated that the flux of threonine with E. coli TRFC‐AP reached 69.8%, an increase of 16.0% compared with that of E. coli TRFC. Overall, higher L‐threonine production and glucose conversion percentage were obtained with E. coli TRFC‐AP due to increased activities of key enzymes and improved carbon flux for threonine synthesis.